Eucalyptus Plantation in Farmlands: A Prospective Source of Economic Returns in Bhabar Terai Zones of Nepal - Neupane, Shiva S (The Initiation, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The Bhabar Terai zone lies immediately at the foot of the Siwalik hills and consist of bouldery and gravelly areas derived from alluvial fans at the base of the hills. Many of the streams flowing from the hills disappear into the very freely drained soil of this area to reappear again in the Terai proper. The soil is not good for the production of food/cereal crops. Eucalyptus species is fast growing and can grow on wide range of climatic conditions. There are special types of farm relations with Eucalyptus in Bhabar Terai. Most of the farmers in this region have Eucalyptus plantations to support their livelihood. It is obvious that Eucalyptus is one of the appropriate tree species to grow in Siwalik and Bhabar zones to get more economic return within the short period of time. Farmers have been accepting to grow Eucalyptus as an integral part of their overall farming systems to maximize their annual income from the same piece of land along with the other tree and cereal crops combinations from the sale of these tree products. Key Words: Bhabar Terai, Eucalyptus plantation, Economic returns, Livelihood support DOI: 10.3126/init.v3i0.2430 The Initiation Vol.3 2009 p.81-85